Pembelajaran kelas ibu hamil terhadap pengetahuan dan sikap ibu tentang pencegahan anemia dan Kurang Energi Kronis (KEK) - Meliani Sukmadewi Harahap; Lina Lina; Nora Veri; Fazdria Fazdria; Susi Arli; Nurhayati Nurhayati (Politeknik Kesehatan Kemenkes Aceh, 2023)
Background: Pathological conditions during pregnancy and until childbirth are important to pay attention to. One form of education is through pregnant women, which is a form of prenatal education that can increase their knowledge, attitude change, and positive behavior of pregnant women about anemia and Chronic Energy Deficiency (CED). Thus, every mother can conduct pregnancy and childbirth examinations for the health workers. The aim was to reduce maternal and child mortality rates.Objectives: This study aimed to measure the effect of pregnant women's class learning on their knowledge and attitudes about anemia and CED prevention. Methods: The study was a quasi-experiment using the one-group pretest-posttest design approach, with a sample size of 55 pregnant women taken randomly. The study was conducted from June to July 2019 at the Banda Mulia Aceh Tamiang Health Center. Data collection of knowledge and attitudes was conducted using direct interview techniques and questionnaire instruments. Statistical analyses were performed using a Dependent T-test with a significance level of 95%.Results: After the intervention, most of the pregnant women had good knowledge (61,8%) and positive attitudes (87,3%). There was an effect of class learning for pregnant women on knowledge (p= 0,042) and attitudes (p= 0,038) regarding the prevention of anemia and chronic energy deficiency (CED).Conclusion: Classroom learning for pregnant women improves their knowledge and attitudes regarding the prevention of anemia and chronic energy deficiency.